Assessment of Diastolic Function in Congenital Heart Disease - Panesar, Dilveer Kaur; Burch, Michael (Frontiers in Cardiovascular Medicine, 2017)
Diastolic function is an important component of left ventricular (LV) function which is often overlooked. It can cause symptoms of heart failure (HF) in patients even in the presence of normal systolic function. The parameters used to assess diastolic function often measure flow and are affected by the loading conditions of the heart. The interpretation of diastolic function in the context of congenital heart disease requires some understanding of the effects of the lesions themselves on these parameters. Individual congenital lesions will be discussed in this paper. Recently, load-independent techniques have led to more accurate measurements of ventricular compliance and remodelling in heart disease. The combination of inflow velocities and tissue Doppler measurements can be used to estimate diastolic function and LV filling pressures. This review focuses on diastolic function and assessment in congenital heart disease.